A content analysis of sports and energy drink advertising. (1st July 2022) - Bleakley, Amy; Ellithorpe, Morgan E.; Jordan, Amy B.; Hennessy, Michael; Stevens, Robin
Abstract: This study identifies constructs from key persuasion theories that are present in popular sports and energy drink advertising. A theory-driven content analysis was conducted on 315 popular television and social media sports and energy drink advertisements from top selling brands. The advertisements were analyzed for the presence of persuasive cues as per the Elaboration Likelihood Model (e.g, onscreen consumption, presence of celebrities) as well as Reasoned Action behavioral expectancies and normative beliefs Approach related to consumption. Descriptive statistics were calculated. Differences between sports and energy drinks were assessed and reliability statistics for all codes were calculated. Advertisements relied on peripheral cues like sports and celebrities that were not related to the drinks themselves. Theory-relevant beliefs about improved athletic performance and consumption of the drinks onscreen were common. Sports drinks were more likely to focus on mainstream sports; energy drinks featured extreme sports, and energy drink advertisements promoted the drinks for use beyond sports (e.g., work settings). The cues and beliefs identified in these ads help to clarify the role of advertising in beliefs about sports drinks being healthy and energy drinks being helpful to achieve goals. Future research is needed that links exposure to coded advertisement features to adolescents' beliefs about sports and energy drinks.